A CLINICAL STUDY ON THE THERAPEUTIC EFFECT OF DHATRYADI KWATHA & APARAJITHA LEPA IN SWITRA IN CHILDREN - Injamuri, *Radhika; Mudadla, Suryanarayana (International Journal of Ayurveda and Pharma Research, 2016)
Vitiligo is one of the skin diseases causing cosmetic problem. It is a common puzzling disorder of great socio-medical importance characterized by hypo pigmented and/or depigmented milky white or ivory white maculae on the skin, resulting from the loss of cutaneous melanocytes. It affects approximately 1-4% of world population in both sexes equally. It inflates an inferiority complex in the person affected. The exact cause of Vitiligo remains obscure, auto immunity may play a role in the development of the disease. It is a challenging problem to all systems of medicine. Modern science treats it with topical & systemic photo chemotherapy, corticosteroids & skin grafting which is costly and not much effective added with more side effects. Based on the clinical features of Switra, it can be correlated to Vitiligo of the Modern medicine In order to evaluate an ideal management for the relief and cure of Switra, an attempt has been made in this work to establish the therapeutic potentialities of Dhatryadi Kwatha & Aparajitha Lepa in Switra. The Yoga, Dhatryadi Kwatha derives its reference from a renowned classic- chakradhatta and Aparajitha lepa from Rajamarthanda. 30 children with Switra were taken up for the study of age between 0-16years and were given treatment for 3 months consisting of external application with Aparajitha lepa and internal medication with Dhatryadi Kwatha. The study has been subjected to statistical analysis, in which the results were found to be significant.